Determinants of Private Investment in the Agricultural Sector of Mozambique (2003-2017) - Isaque Manteiga Joaquim; Raitone Armando; Enia Pondo; Elzira Tundumula (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2022)
Shortly after independence, Mozambique's economy was characterized predominantly by a public investment over private investment until roughly 1986. In this period, the public sector was seen as the main economic agent, centralizing most of the available resources. Bearing in mind that investment is one of the main components of aggregate demand and source of long-term economic growth, its fluctuations affect significantly the overall functioning of an economy and agriculture in particular. It's in this perspective the study comes in to unfold and understand the major determinants of the private investment in agriculture, as well as the constraints that represent the main challenges to invest in this sector due to the scarcity of capital. The study carried out an analysis of a theoretical approaches from exploratory, bibliographic combined with quantitative method based on the macroeconomic models (the neoclassical model, the flexible accelerator model, and the options model) to address the question of the study. And to achieve our objectives, the sample referred to the period of 2003-2017 and the choice of that period is associated, among several factors the consistency and availability of data on the variables included in the model such as the real GDP; GDP of the agrarian sector; public investment (government spending on infrastructure, electricity, water, between others); real interest rate; inflation rate (a variable capturing the effects of uncertainty from macroeconomic instability on the level of investments) and arable land.The results showed that the agrarian sector is influenced by the wealth produced from engineering sector (infrastructure).Keywords: Determinants, Investment, Private Investment, Agricultural Sector, Economy